Clinico-microbial profile in chronic suppurative otitis media and its management in tertiary care centre - Ramashesh, Rashmi; Wajid, Samira Abdul; Chandra, Smitha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Chronic suppurative otitis media (CSOM) is an ever growing concern of preventable hearing loss and is a major health concern especially in tropical countries. Lack of cleanliness, overcrowding, poverty, malnutrition and medical ignorance are few of the contributing factors. The microbiological flora is constantly changing due to indiscriminate use of antibiotics with rapid change in the antibiotic sensitivity patterns. Hence, this study was undertaken to determine the epidemiological profile, bacteriological profile and the antibiotic sensitivity pattern which would help in establishing a protocol in management of CSOM patients in the hospital. Methods: A total of 100 patients of CSOM attending the ENT Outpatient Department of The Oxford medical College, Hospital and Research Centre were included in the study. The samples were immediately sent to the Microbiology laboratory for further processing according to standard procedure. Results: Out of 100 cases, 74 were active mucosal type and 26 were active squamous, with Pseudomonas species (33.6%) being the predominant organism. Staphylococcus aureus was the next common organism with MSSA (16.3%) and MRSA (12.5%), CONS were 6.7%. Among the 28 gram-negative bacilli, Klebsiella pneumoniae (7.7%), was followed by Escherichia coli (5.7%), and Proteus mirabilis (4.8%). Conclusions: Pseudomonas species and Staphylococcus aureus are the commonest organisms of CSOM. Ciprofloxacin can be used as a topical agent for treating gram-negative bacilli. Among systemic antibiotics- Linezolid, Amikacin and Imepenam remains the drug of choice.